2013
DOI: 10.4049/jimmunol.1202824
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Infection Impairs Mycobacteria-Specific T Cell Responses and Mycobacterial Clearance in the Lung during Pulmonary Coinfection

Abstract: Individuals infected with mycobacteria are likely to experience episodes of concurrent infections with unrelated respiratory pathogens, including the seasonal or pandemic circulating influenza A virus strains. We analyzed the impact of influenza A virus and mycobacterial respiratory coinfection on the development of CD8 T cell responses to each pathogen. Coinfected mice exhibited reduced frequency and numbers of CD8 T cells specific to Mycobacterium bovis bacille Calmette-Guérin (BCG) in the lungs, and the IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Mouse models have shown that prior exposure to influenza A impairs immune responses to Mtb infection and decreases survival (Redford et al 2014), possibly through down-regulated MHC (major histocompatibility complex) expression on dendritic cells and reduced activation of CD4 and CD8 T cells to clear mycobacteria (Florido et al 2013). A similar murine study found influenza had little effect on mycobacterial load (Co et al 2006).…”
Section: Influenzamentioning
confidence: 72%
“…Mouse models have shown that prior exposure to influenza A impairs immune responses to Mtb infection and decreases survival (Redford et al 2014), possibly through down-regulated MHC (major histocompatibility complex) expression on dendritic cells and reduced activation of CD4 and CD8 T cells to clear mycobacteria (Florido et al 2013). A similar murine study found influenza had little effect on mycobacterial load (Co et al 2006).…”
Section: Influenzamentioning
confidence: 72%
“…Mice models have shown that co-infection with influenza and Bacillus Calmette–Guérin in the lung led to exacerbation of the pulmonary disease and that pulmonary co-infection with influenza reduces production of protective T cell responses against intracellular mycobacterium [30]. A case series of patients who died during the 2009 influenza pandemic in South Africa described underlying tuberculosis in 10% of deaths which was greater than the population prevalence of tuberculosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of IAV infection, CD4 + T‐cell help is essential for the development of the memory CD8 + T‐cell response and both IAV‐specific CD8 + and CD4 + T cells persist lifelong. In our previous work, infection of mice with a recombinant influenza A virus (rIAV) expressing the CD8 + epitope of the M. tuberculosis MPT64 protein (MPT64 190–198 ) induced a strong pulmonary epitope‐specific CD8 + T‐cell response that persisted in the lung long after viral clearance . This suggests that rIAVs may be useful tools to induce M. tuberculosis epitope‐specific CD4 + and CD8 + T‐cell responses in the lung and to analyze their role in protection against M. tuberculosis .…”
Section: Introductionmentioning
confidence: 99%